Perceived Security and Trust as Mechanisms of P2P Adoption Technology: Evidence from Pre-Adopters Using PLS-SEM Approach - Indra Dharma Wijaya; Rudi Salam; Saiful Ghozi; Faiz Ushbah Mubarok; Muhamad Fajar Subkhan (International Journal of Environment, Engineering and Education, 2026)
Peer-to-peer (P2P) lending can expand working-capital access for micro-entrepreneurs, yet borrowing via digital platforms heightens perceived vulnerability due to sensitive data disclosure and binding repayment obligations. This study examines how perceived security and trust shape adoption intention in a high-stakes fintech context by extending the Technology Acceptance Model (TAM) and testing whether security and trust transmit the effect of perceived usefulness to intention. Using an explanatory cross-sectional design, we collected offline-administered survey data from 204 Indonesian micro-entrepreneurs who had not previously adopted P2P lending to capture pre-adopter perceptions better and reduce digital-selection bias. The model was estimated using PLS-SEM 3. The results indicate that all hypothesized relationships are positive and statistically significant. Perceived usefulness significantly enhances perceived security (β = 0.562) and trust (β = 0.259), while perceived security exerts a strong positive effect on trust (β = 0.517). Intention to use P2P lending is directly influenced by perceived security (β = 0.337), trust (β = 0.213), and perceived usefulness (β = 0.208). Mediation analysis confirms that perceived security (β = 0.189) and trust (β = 0.055) partially mediate the effect of perceived usefulness on intention to use. The model explains 42.4% of the variance in intention to use (R-squared = 0.424) and demonstrates adequate predictive relevance (Q-squared = 0.263). Overall, perceived security emerges as the most influential determinant of adoption intention, underscoring the importance of security-by-design features, transparent governance, and robust consumer-protection frameworks in fostering trust and accelerating P2P lending adoption among micro-entrepreneurs.